If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10g + 50 = 2g + 18 Reorder the terms: 50 + 10g = 2g + 18 Reorder the terms: 50 + 10g = 18 + 2g Solving 50 + 10g = 18 + 2g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-2g' to each side of the equation. 50 + 10g + -2g = 18 + 2g + -2g Combine like terms: 10g + -2g = 8g 50 + 8g = 18 + 2g + -2g Combine like terms: 2g + -2g = 0 50 + 8g = 18 + 0 50 + 8g = 18 Add '-50' to each side of the equation. 50 + -50 + 8g = 18 + -50 Combine like terms: 50 + -50 = 0 0 + 8g = 18 + -50 8g = 18 + -50 Combine like terms: 18 + -50 = -32 8g = -32 Divide each side by '8'. g = -4 Simplifying g = -4
| 3/4x=3/1 | | -6(5r-6)+4r= | | 120=9 | | -8x+x=14 | | 1/3(3.14)(36)(4) | | 8-5w=-23 | | 3.8w+3.2=2.4(w+4) | | 15=6m-3 | | (1/2)x=(9/14)x+(1/7) | | 6-7x=-5x-18 | | 6x+3=p | | (x*x)=5/2 | | z/3=-1/6 | | -9x+8=3x-16 | | 9x-4x+136=9x+80 | | 8(8n-4)-1=-289 | | 7m-50+3m=100+8m | | 9x-4x+136=9x+180 | | 45=9 | | x/3=-1/6 | | b-4.7=2.1 | | 3-r=2 | | -1=-8+x/8 | | 4x-2=-2x+22 | | z^3+4=z^2+4z | | 25=9 | | z^3+4=z | | F(x)=5x^2-10x-4 | | 7x+18-6x=-8-12 | | 1/27h=28 | | 4i+6=-1-4 | | 18x+-5=3(6x+-2) |